2019
DOI: 10.1177/2167702619838464
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Imminent Suicidal Thoughts and Nonfatal Attempts: The Role of Complexity

Abstract: For decades, our ability to predict suicidal thoughts and behaviors (STBs) has been at near-chance levels. The objective of this study was to advance prediction by addressing two major methodological constraints pervasive in past research: (a) the reliance on long follow-ups and (b) the application of simple conceptualizations of risk. Participants were 1,021 high-risk suicidal and/or self-injuring individuals recruited worldwide. Assessments occurred at baseline and 3, 14, and 28 days after baseline using a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 43 publications
5
80
0
3
Order By: Relevance
“…Because our suicide-risk meta-analysis may have been driven by differences in SI, our results may suggest that differences in severity of SI can be due to disruptions in neural systems. This suggestion aligns with recent work suggesting that the number of paths leading to SI is indeterminate (Huang, Ribeiro, et al, 2020;Ribeiro et al, 2019). Another possibility is that what has been termed the general factor of psychopathology, or p factor, is driving this lack of differences (Caspi et al, 2014;Lahey et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Because our suicide-risk meta-analysis may have been driven by differences in SI, our results may suggest that differences in severity of SI can be due to disruptions in neural systems. This suggestion aligns with recent work suggesting that the number of paths leading to SI is indeterminate (Huang, Ribeiro, et al, 2020;Ribeiro et al, 2019). Another possibility is that what has been termed the general factor of psychopathology, or p factor, is driving this lack of differences (Caspi et al, 2014;Lahey et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Both studies focused on a clinical sample that is different from the target group of the current study. Another study that can be comparable to our study is Ribeiro and colleagues [ 44 ]. Although it showed a good performance (AUC: 0.9), the population was different (adults with a history of self-injury), and it did not focus on important psychological variables that have been shown to be related to suicide, such as positive mental health, post-traumatic stress disorder, and post-traumatic growth.…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, research using the D-IAT has found that these self-identification tendencies prospectively predict suicide attempts over a six-month follow-up, above and beyond a history of a prior suicide attempt as well as both clinicians' and patients' predictions of engaging in a suicide attempt (Nock et al, 2010). Other studies have found similar prospective prediction results with reduced identification with life/increased identification with death associated with greater risk (Randall, Rowe, Dong, Nock, & Colman, 2013;Tello, Harika-Germaneau, Serra, Jaafari, & Chatard, 2019).…”
Section: Introductionmentioning
confidence: 88%